2014
DOI: 10.3109/19390211.2014.901999
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Stevia Rebaudiana on Serum Omentin and Visfatin Level in STZ-Induced Diabetic Rats

Abstract: Recently the role of adipocytokines in relationship to incidence of diabetes has been demonstrated. One of the medicinal plants that are used in the treatment of diabetes is stevia. This study investigates the effect of stevia on serum omentin and visfatin levels as novel adipocytokines in diabetic induced rats to find potential mechanisms for the anti hyperglycemic effect of stevia. Forty male wistar rats weighing 180-250 g were induced with diabetes by intraperitoneal injection of streptozotocin (STZ). The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
20
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 31 publications
9
20
0
2
Order By: Relevance
“…Previous reports on thyroid function in diabetic rats were inconsistent and there was no intensive exploration of HPT axis function. Our results showed significantly lower T3 and T4 levels in diabetic group than those in NC group, which was consistent with previous results [ 18 21 ]. We also detected no significant difference on the levels of TSH and pro-TRH mRNA between normal and DM group, which were in line with results of Nascimento-Saba et al [ 20 ] and Derkach et al [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous reports on thyroid function in diabetic rats were inconsistent and there was no intensive exploration of HPT axis function. Our results showed significantly lower T3 and T4 levels in diabetic group than those in NC group, which was consistent with previous results [ 18 21 ]. We also detected no significant difference on the levels of TSH and pro-TRH mRNA between normal and DM group, which were in line with results of Nascimento-Saba et al [ 20 ] and Derkach et al [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…We also detected no significant difference on the levels of TSH and pro-TRH mRNA between normal and DM group, which were in line with results of Nascimento-Saba et al [ 20 ] and Derkach et al [ 22 ]. However, Akbarzadeh et al detected that TSH in diabetic rats induced by 55 mg/kg STZ was even higher than that of NC group [ 18 ], and similar result was proved in other studies using low-dose STZ (30–40 mg/kg) to induce mild diabetic model [ 22 , 23 ]. The discrepancies might be related to the dose and manner of STZ administration in diabetes model.…”
Section: Discussionsupporting
confidence: 56%
“…Chemical composition: The chemical composition of Stevia rebaudiana Bertoni leaves powder indicated that moisture, crude protein, crude fat, crude fiber, crude ash and carbohydrates were 9.7 ± 0.04 %, 10.23 ± 0.07 %, 14.87 ± 0.10 %, 4.15 ± 0.16 %, 9.65 ± 0.19 % and 51.4 ± 0.32 % respectively ( Table 1). The results are in accordance with the studies of [7,21] who stated that moisture, ash, protein, fat, fiber and carbohydrates in Stevia rebaudiana Bertoni dried leaves powder were in the ranges of 7.35-10.73%, 12.06-13.12%, 13.68-16.92%, 0.5-6.13%, 5.03-10.12% and 57.59-63.1% respectively.…”
Section: Characterization Of Stevia Leaves Powdersupporting
confidence: 92%
“…The carbohydrates in stevia leaves powder muffins decreased as compared to control because stevia contained zero calories. The fat content in functional muffins increased than control but the difference was not pronounced because stevia has less amount of fat content as recorded in the previous literature [7,21]. T 0 = 100% sucrose T 1 = 25% stevia leaves powder: 75 % sucrose T 2 = 50% stevia leaves powder: 50 % sucrose T 3 = 75% stevia leaves powder: 25 % sucrose T 4 = 100% stevia leaves powder Where 1g of stevia leaves powder= 20 g of sucrose T 0 = 100% sucrose T 1 = 25 % stevia leaves powder: 75% sucrose T 2 = 50 % stevia leaves powder: 50% sucrose T 3 = 75 % stevia leaves powder: 25% sucrose T 4 = 100 % stevia leaves powder Where 1g of stevia leaves powder=20 g of sucrose with mean values as (120.02 ± 0.77-1300.03 ± 0.80 ppm), (90.05 ± 0.60-660.04 ± 0.88 ppm), (32.10 ± 0.54-250.03 ± 0.82 ppm), (21.11 ± 0.27-180.04 ± 0.77 ppm) and (2.00 ± 0.03-11.07 ± 0.08 ppm) respectively.…”
Section: Chemical Analysis Of Functional Muffinsmentioning
confidence: 52%
“…According to Akbarzadeh et al . (), an increase in omentin serum was observed in rats with experimental diabetes induced by STZ. Nevertheless, the exact role of omentin is not well described in the literature.…”
Section: Discussionmentioning
confidence: 85%